Seção Técnica de Administração e Desenvolvimento de Recursos Humanos - STDARH - Bonilha, José Luiz; Matos, Zilda Aparecida Gonçalves; Matos, Zilda Aparecida Gonçalves; Rocha, Osni Donisete da; Matos, Zilda Aparecida Gonçalves; Rocha, Osni Donisete da; Micheletto, Cláudia; Pereira, Doraci Aparecida; Rocha, Osni Donisete da; Caetano, Verci Fernando Constantino; Micheletto, Cláudia; Micheletto, Cláudia; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - José Luiz Bonilha